Construction of foundation piles, diaphragm walls and other related works for 13 storied (with 3 basements) institutional building for brac university at holding No. Kha 224, Merul Badda, Dhaka-1212 - Brac University (Brac University, 2024)
This tender document is made between Brac University and web structures for construction of foundation piles, diaphragm walls and other related works for 13 storied (with 3 basements) institutional building for Brac University new campus project.